2016
DOI: 10.1186/s12981-015-0084-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the first antiretroviral therapy modification in older HIV-1 positive patients

Abstract: BackgroundRates of first antiretroviral therapy (cART) modifications are high in most observational studies. The age-related differences in treatment duration and characteristics of first cART modifications remain underinvestigated. With increasing proportion of older patients in HIV population it is important to better understand age-related treatment effects.MethodsPatients were included into this analysis, if being cART naïve at the first visit at the clinic. Follow-up time was measured from the first visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In line with other reports this study confirms that, besides the ARV chosen, certain baseline characteristics of patients are independently associated with differences in treatment duration [ 27 30 ]. In naive patients we found that AIDS diagnosis and the use of other backbone than ABC/3TCor TDF/FTC increased the risk for early treatment discontinuation.…”
Section: Discussionsupporting
confidence: 92%
“…In line with other reports this study confirms that, besides the ARV chosen, certain baseline characteristics of patients are independently associated with differences in treatment duration [ 27 30 ]. In naive patients we found that AIDS diagnosis and the use of other backbone than ABC/3TCor TDF/FTC increased the risk for early treatment discontinuation.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, there was no difference in ART modification by age group over time in the overall adjusted Cox regression analysis. Studies from high-income regions have shown conflicting results regarding the association of older age and need for ART modification with some studies indicating a decreased risk of regimen switch and others showing an increased likelihood with older age [39,40]. Studies that have shown increased risk of ART modification for older adults have attributed the observation to higher rates of drug toxicities and adverse events [40].…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to other European cohorts [ 18 , 19 ]. Previous published Polish data were limited to single-centre cohort observed until February 2013 and indicated higher frequency (72.4%) of protease inhibitor use with similar percentage of NNRTI used (26.1%) and infrequent treatment with integrase inhibitors (<1.5%) [ 20 ]. Integrase inhibitors were introduced in Poland in 2008 with raltegravir, elvitegravir containing regimens in 2012 and dolutegravir in 2014.…”
Section: Discussionmentioning
confidence: 99%